Material of Choice in Pediatric Cranioplasty - Salam, Anooja Abdul; Ibbett, Imogen; Thani, Nova (Indian Journal of Neurosurgery, 2021)
Background Current evidence is lacking regarding the optimum material required for cranioplasty in the pediatric population when native bone cannot be replaced. The aim of our survey was to examine current practice in Australia and New Zealand regarding pediatric cranioplasty material.Methods The online tool SurveyMonkey was used to survey 244 neurosurgeons in Australasia. The survey consisted of five questions concerning preference of material and donor origin for pediatric cranioplasty.Results Twenty-two neurosurgeons (9%) participated. The results indicate that with small skull defects (< 3 cm) in patients aged 0 to 2years, conservative management with observation alone is the preferred option (65%). In patients aged 3 to 10 years, autologous donor bone was the most popular option, whereas for 11+ years, hydroxyapatite (HA) was the material of choice, followed by titanium. For defects of more than 3 cm, autologous donor bone was preferred in under 11 years. In patients older than 11 years, titanium was the preferred choice (46.67%). The preferred donor origin for autologous cranioplasty in small skull defects (< 3 cm) was split calvarial grafts for all age groups. However, 68.42% of respondents managed those under 2 years conservatively. In large skull defects (> 3 cm), the preferred donor origin was split calvarial grafts for patients older than 3 years (48.3%). In patients aged 0 to 2 years, exchange cranioplasty was the preferred option when cranioplasty was performed.Conclusion The current practice in Australia and New Zealand is to use autologous donor bone in preference to synthetic materials for cranioplasty in children under 11 years. In children older than 11 years, hydroxyapatite and titanium are the materials of choice.
Keywords: pediatric cranioplasty; autologous; donor graft origin; synthetic cranioplasty material; survey